2010
DOI: 10.1088/0963-0252/19/3/034017
|View full text |Cite
|
Sign up to set email alerts
|

Radical surface interactions in industrial silicon plasma etch reactors

Abstract: Silicon etching in Cl 2 -based plasmas is an important step for the fabrication of IC circuits but the plasma surface interactions involved in this process remain poorly understood. Based on the developments in plasma and reactor wall diagnostics, this paper reviews the recent progress in the understanding of radicals' interactions with surfaces during silicon etching processes. X-ray photoelectron spectroscopy analysis of the reactor walls shows that during Si etching in Cl 2 /O 2 plasmas, the initial Al 2 O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 50 publications
6
49
0
1
Order By: Relevance
“…5, the neutral atoms temperature of the magnetron plasma T a , which corresponds to the L r T value deduced from the two temperature fitting 25,26 , is 320 K; the 6 rotational distribution in the high J levels being represented by H r T =1500 K. For gas pressures of 0.6, 4.5 and 14 µbar, the T a deduced from the recorded nitrogen spectra at different discharge powers are plotted in figure 6 and range between 300 and 380 K. Values at intermediate pressures can be deduced by the interpolation of these data. As expected, at fixed pressure, T a increases with the dissipated power, but also slightly with the gas pressure 21 . From the measurement of the Cu emission linewidth with a Fabry-Perot interferometer, Ball et al have reported a comparable gas temperature of 350 K in a dc copper magnetron discharge running with argon gas 27 .…”
Section: -Gas Temperaturesupporting
confidence: 82%
See 1 more Smart Citation
“…5, the neutral atoms temperature of the magnetron plasma T a , which corresponds to the L r T value deduced from the two temperature fitting 25,26 , is 320 K; the 6 rotational distribution in the high J levels being represented by H r T =1500 K. For gas pressures of 0.6, 4.5 and 14 µbar, the T a deduced from the recorded nitrogen spectra at different discharge powers are plotted in figure 6 and range between 300 and 380 K. Values at intermediate pressures can be deduced by the interpolation of these data. As expected, at fixed pressure, T a increases with the dissipated power, but also slightly with the gas pressure 21 . From the measurement of the Cu emission linewidth with a Fabry-Perot interferometer, Ball et al have reported a comparable gas temperature of 350 K in a dc copper magnetron discharge running with argon gas 27 .…”
Section: -Gas Temperaturesupporting
confidence: 82%
“…A very reliable method to obtain the gas temperature is from the linewidth of the Doppler-broadened absorption profile of a specific line, measured with a single-mode tunable diode laser. Absorption from argon metastable atoms is particularly popular in pure argon plasmas 17,18,19,20 or by adding a small amount of argon to the halogen based plasmas 21 . Another commonly used technique consists of adding a small amount of a diatomic molecule, very often N 2 , to the plasma and on the measurement of its rotational temperature.…”
Section: -Gas Temperaturementioning
confidence: 99%
“…21,22 The latter is equal to the neutral gas temperature. To perform this measurement, the laser beam is attenuated to the power of a few lW and its wavelength is scanned in the vicinity of the transition center.…”
Section: Methodsmentioning
confidence: 99%
“…The gas temperature identifies the flow-out rate. If it is not properly defined in the pulse off region, the mass flow drains excessive amount of species from the chamber with the pulse on value of 800 K. Regarding this, we estimate a cooling time-scale about 20 ms that is based on the observations by Cunge et al [61,62]. In this respect, we assume that the gas temperature drops to the ambient temperature in 20 ms.…”
Section: Experimental Comparisonmentioning
confidence: 99%